IMPLEMENTATION OF A VEHICLE MONITORING SYSTEM AT PT JAYA BUANA PERKASA - Nawawi, Agus; Pramudita, Rully (Antivirus : Jurnal Ilmiah Teknik Informatika, 2025)
Operational vehicle security is a very important aspect in supporting the smooth running of company activities, especially for PT Jaya Buana Perkasa which is engaged in information technology services. This study aims to design and implement an Internet of Things (IoT)-based vehicle security system using Arduino Nano devices, SIM800L modules, and GPS Neo-6M. The system is designed to receive commands via SMS messages to remotely control the vehicle engine and provide location information directly. The system development uses a prototype method, while the testing process is carried out through a black box approach and user evaluation. The test results show that the system is able to respond to commands well, regulate relays for engine control, and send location information with adequate accuracy. This system provides a real solution in improving vehicle security and the efficiency of operational fleet management